Estudio de factibilidad para la creación de una empresa dedicada a la producción y comercialización de manjar de leche de soya en la ciudad de Loja - Uchuari Merino, Jorge Jimmy (2018)
The present investment project, has the main objective of determining the feasibility for the creation of a company dedicated to the production and marketing of soy milk delicacy in the city of Loja, which will serve as a guide to generate a new business project that provides to society a new and innovative product that leads to improve the eating habits of the population. For the execution of this project, it was necessary to use quantitative, descriptive and analytical methods, as well as the techniques of data collection such as the survey, interview and direct observation. Within the first objective is the market study where it starts with sampling for the application of surveys for the population of medium / high socioeconomic level of 2017, when performing the calculation of sampling it was obtained that for the market investigation it was I would take a sample of 372 families to survey. Based on the results obtained, the market study determined that the potential demand of the delicacy in the city of Loja for the first year is 78% of potential consumers, the average consumption of delicacies is 14 pounds per family per family, the real demand it is 47% and the effective demand was a total of 91%. The offer in the market was determined through the application of the interview to the main points of sale in the city such as supermarkets, supermarkets, shopping centers and others, where a total of 4,290 pounds per year was obtained from the milk supply Soybean of the SOYMILKE brand and 10% of the production of the cacera. In this way the unmet demand was determined giving a total of 53,085 pounds of soy milk delicacy, finally through the market study the company's marketing plan was established through strategies according to the product, place 6 and distribution of the product. , the price and advertising to enter to compete in the market. The technical study was also carried out where it was established that the installed capacity of the company is 122,640 units and the capacity used is 29,120 units, for the first year it operates at 80% capacity used. The company will be located in the parish of El Valle, the band sector, on Avenue December 8. In the engineering of the project, the production process is defined, where it is established that for each hour of the process, 14 pounds of soy milk and 112 pounds of milk will be produced, taking full advantage of the company's technological resources. It was defined through the administrative study that the company will be limited liability under the name of "JORSOYA CIA. LTDA ", will have 3 partners who will contribute the capital stock, in addition to a bank loan to cover the total investment, the organizational structure of the company and the respective function manuals for the staff that will operate the new productive unit. Through the financial study it was determined that to start the activities of the company you need own or social capital of $ 18.765,36, which represents 65% of the investment and an external capital or credit of $ 10,000, with an interest of 11% Annual, which represents 35% of the investment, will be financed by the bank BAN ECUADOR. Through the cost analysis, the retail price was determined, resulting in the product being sold in the first year at $ 2.50 per presentation of 1 pound. Finally the financial evaluation of the project was carried out to know the feasibility or not of the same through the financial indicators such as; the Net Present Value (NPV) which obtained a positive result of $ 10.732,40, the Internal Rate of Return 7 (IRR) was 25.21% higher than the opportunity cost, the Cost Benefit Ratio (RBC) was obtained that for each dollar invested you get 26 cents of return, the Period of Recovery of Capital (PRC) was established that the investment will recover in 3 years 11 months and 13 days, finally the analysis of sensitivity with increase in costs is 7,91% and sensitivity analysis with decrease in income is 6,33%, so the project is not sensitive to these variations that may influence profitability. Finally, it is concluded that the present investment project through the realization of the pertinent studies, has been determined that it is feasible for its implementation and its execution is recommended since it foresees that profitability and economic benefits will be obtained as soon as the operational phase of the company.